Tourists’ Perception of Ecotourism Development in Lagos Nigeria: The Case of Lekki Conservation Centre. - Nwokorie, Edwin Chigozie; Adeniyi, Eneloke Esther (Turizam, 2020)
This study examined tourists’ perception of ecotourism services in Lagos, Nigeria, with the specificity of Lekki Conservation Centre. Specific objectives were to identify the elements of tourists demand in relation to destination loyalty in the study area. A total of 300 domestic and inbound tourists were sampled, over a period of ten months, using a structured questionnaire. Descriptive statistics were used for data analysis. The findings revealed an availability of vital tourism related products to meet tourist demand, a conducive tourism atmosphere and a dispersed location of the species in the conservation center with the availability of quality tourism facilities.  However, tourists’ perception and experience were poor compared to available infrastructural components. The study concludes that managers of the centre have not employed quality destination management and marketing techniques to improve its image and enhance inbound tourism. Recommendations included the need for provision of more facilities and species, and an improved means of transportation to enhance tourist accessibility to the centre.
Keywords: destination image; destination loyalty; ecotourism; inbound tourism; sustainable tourism; tourist destination